(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This paper delves into the theoretical underpinnings of weaker forms of normality in topological spaces. Normality is a fundamental concept in topology, providing a foundation for many theorems and results. However, in certain contexts, the assumption of full normality might be too strong. We explore various weaker forms of normality, such as regularity, semi-normality, and other related concepts, investigating their properties, relationships, and implications in the realm of topology. This paper aims to provide a comprehensive overview of these theoretical approaches, shedding light on their significance and applicability in mathematical analysis.